Necrotizing Fascitis- A Tale of Two Cases - Sarandeep Singh Puri; Suparna Dubey; Monal Trisal; Jyoti Mishra; Gurleen Gill; Shubhangi Gupta (Dr. Annil Mahajan, 2022)
Necrotizing fasciitis (NF) is a rare dangerous life-threatening disorder which is caused by a bacterial infection. This fulminant infection causes widespread necrosis of the skin, subcutaneous tissue, and superficial fascia and necrotizing soft tissue infection along fascial planes with or without overlying cellulitis. We report two cases of necrotising fasciitis in young patients; one 8 months old female infant and the other 21 years old male. Both the cases were diagnosed on Histopathology.